2017
DOI: 10.1007/s11356-017-0218-5
|View full text |Cite
|
Sign up to set email alerts
|

Integration of soil magnetometry and geochemistry for assessment of human health risk from metallurgical slag dumps

Abstract: The main objective of the study was an assessment of the pollution level of agricultural land located close to dumps of industrial waste remaining after former Zn and Pb ore processing in Poland. The integrated geophysical-geochemical methods were applied for assessment of soil quality with respect to trace element pollution. Additionally, human health risk induced by the contaminated arable soil and dusting slag heap was estimated. The investigations pointed out that soils in the vicinity of the metallurgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…11a). A similar effect was also observed in the area of the post-industrial waste dumping ground of zinc and lead smelter in Piekary (Rachwał et al 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…11a). A similar effect was also observed in the area of the post-industrial waste dumping ground of zinc and lead smelter in Piekary (Rachwał et al 2017).…”
Section: Discussionsupporting
confidence: 76%
“…The weathering processes cause the iron to pass from the paramagnetic forms to the ferri-or antiferrimagnetic forms, which results in an increase in the value of magnetic susceptibility. The research (Rachwał et al 2017;Magiera et al 2018) showed a high correlation between the magnetic susceptibility values and Zn, Mn, Cu, As and Sb, the potentially toxic elements (PTEs) characteristic for emissions associated with storage and processing of Zn-Pb ores.…”
Section: Introductionmentioning
confidence: 99%
“…Such conditions are very favorable for the application of geophysical measurements based on magnetic and geoelectric methods in order to more accurately determine the depth of the metallurgical waste layer, which in a significant part of the park creates the subsoil for Technosol occurring in this area. Soil magnetometry (initially tested in this park area for pollution screening) is suitable for identifying soil pollution connected with airborne deposition of technogenic magnetic particles and related trace elements, and it is limited to the uppermost layers of the topsoil (Hanesch & Scholger, 2002; Magiera, Strzyszcz, & Rachwał, 2007; Petrovský, Kapička, Jordanova, Knab, & Hoffmann, 2000; Rachwał, Wawer, Magiera, & Steinnes, 2017; Strzyszcz, Magiera, & Heller, 1996). In many cores collected in the area of magnetic anomaly, the κ value measured at a depth of 30 cm was still high.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the other analyzed metals, their content in the metallurgical waste is low, significantly below the thresholds provided by law (Table S2). it is limited to the uppermost layers of the topsoil (Hanesch & Scholger, 2002;Magiera, Strzyszcz, & Rachwał, 2007;Petrovský, Kapička, Jordanova, Knab, & Hoffmann, 2000;Rachwał, Wawer, Magiera, & Steinnes, 2017;Strzyszcz, Magiera, & Heller, 1996). In many cores collected in the area of magnetic anomaly, the κ value measured at a depth of 30 cm was still high.…”
Section: Physicochemical Characterization Of Metallurgical Wastesmentioning
confidence: 98%
“…Nowadays, it is nearly impossible to find an area in this region that has not been transformed by human activity. As such, soils in this area have been strongly transformed and contaminated [ 17 , 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%